Analisis Situasi Stunting dan Perencanaan Program Pencegahan Stunting di Wilayah Kerja Puskesmas Suak Ribee Kecamatan Johan Pahlawan Kabupaten Aceh Barat Tahun 2022–2026 - Anggi Elsha Monica; Khusna Idayati; Surika Surika; Nursani Nursani; Maghfira Maghfira; Asra Gusmaini (Indo Publishing, 2026)
Stunting is a chronic nutritional problem that remains a serious challenge in Indonesia, including in the working area of Suak Ribee Public Health Center, Johan Pahlawan District, West Aceh Regency. Based on SigiziKesga data in April 2026, the prevalence of stunting among the sample group of toddlers reached 90.9%, accompanied by underweight at 81.8% and wasting at 63.6%. This analysis aims to assess the stunting situation and formulate a data-based stunting prevention program plan in the Suak Ribee Public Health Center working area from 2022 to 2026. The method used was secondary data analysis from the SigiziKesga system, Suak Ribee Public Health Center data from 2022 to 2026, and national data such as SKI, Riskesdas, and BPS. Problem prioritization was carried out using the USG Matrix (Urgency, Seriousness, Growth), while the causal analysis used the UNICEF conceptual framework. The results showed that stunting was identified as the main priority problem with the highest USG score of 14. The direct causes of stunting included inadequate nutritional intake and infectious diseases, while the indirect causes included low maternal nutrition knowledge, inappropriate parenting practices, limited access to health services, and poor environmental sanitation. However, there was a decreasing trend in stunting cases, from 20 cases in 2022 to 6 cases in 2026. Therefore, a comprehensive intervention program consisting of nutrition education, supplementary feeding, growth monitoring, and strengthened cross-sector collaboration is needed to accelerate the reduction of stunting in the Suak Ribee Public Health Center working area.